Myelopathy in neonatal and infantile lupus erythematosus. Issue 7 (July 1987) - Kaye, E M; Butler, I J; Conley, S
Abstract : Two children with lupus erythematosus and myelopathy were studied. The first child developed the neonatal lupus erythematosus syndrome associated with transplacentally acquired anti-Ro/SSA antibodies. The cutaneous manifestations of neonatal lupus erythematosus disappeared but a residual myelopathy was confirmed at 16 months of age. The second child developed cutaneous lupus erythematosus at 3 months of age associated with a total deficiency of the Clr component of complement. A myelopathy and mesangial glomerulonephritis developed at 2 years of age which required treatment with corticosteroids. These two children with CNS lupus erythematosus, one associated with transplacentally acquired antibodies and the other associated with a complement deficiency, may suggest an immune-mediated mechanism for the pathogenesis of myelopathy in childhood lupus erythematosus.